Fatty liver in Pakistani cohort with rheumatoid arthritis - Wagan, Abrar Ahmed (Pak J Med Sci, 2020)
OBJECTIVE: To determine the frequency of fatty liver (non-alcoholic) disease, Framingham 10-year cardiovascular risk score in rheumatoid arthritis patients. METHODS: This study was conducted from September 1(st) to March 19, 2019, at Rheumatology OPD, Central Park Medical College Lahore. One hundred ninety two seropositive rheumatoid arthritis patients were recruited. Demographic details were noted, BP, BMI, smoking habits, and waist circumference were noted, then sent to radiology department for ultrasound scan of abdomen by an expert radiologist. On next day 10 ml blood was taken by phlebotomist for lipid profile and fasting blood sugar levels, after availability of results 10-years Framingham cardiovascular risk score was calculated. RESULTS: Females were (81.3%) mean age of (45.4) years, fatty liver was present in n=39 (20.3%). In positive cases comorbid like metabolic syndrome was present (71.8%), diabetes mellitus (33.3%), hypertension (59%) FRS score (intermediate to high in (33.3%), history of hakeem/desi medication use (51.3%), while on regression analysis all study parameters except DMARD’s had significant association with fatty liver (p<0.05). CONCLUSION: Nonalcoholic fatty liver disease is very widely prevalent in rheumatoid arthritis patients. As in general population, it is multifactorial in origin and needs careful monitoring and treatment.